Shift from smart mobility to responsive mobility for metro stations in Chennai, India - Ar. S. Sivaneswari; Dr. D. Karthigeyan (Transactions on Transport Sciences, 2023)
The responsive city explores citizen as centre of decision making in the smart city ideas, that is "From For the citizen to By the citizen". Last-mile connectivity is the connection between stations transit stops, to the final destination. It is one of the major factors in a successful smart mobility plan. This research is an attempt to explore responsive last mile connectivity. The two newly opened station (Tiruvottiyur metro station and Wimco nagar metro station) of Chennai metro rail phase I extension is selected as the study area, which provide wide scope for research. The issues identified and solved at the early stage of the development of transit network will improve the quality of life of citizens and also increase commuters, which has a relationship with economic development on the other hand. Two park analysis was undertaken in this research, one based on the questionnaire survey on five major aspects i.e. exact location of the commuters, General information about the commuters, trip information, parameters of Chennai Metro rail limited, Suggestions and recommendations of commuters and other is the statistical analysis for predicting the mode choice using multinomial logit regression method. From the findings it was evident that lack of quality infrastructure, pedestrian-friendly facility and high peak hour traffic are the major problems felt by the commuters. From the Multinomial logit model it is found that there is an increase in usage of public transport in one station and decrease in the other station. The pure participatory approach was involved in arriving at the proposal from the finding of the analysis in this research.